Eco-Art Diorama as Thematic Learning Media for Early Childhood Education (PAUD) - Nurlaili, Nurlaili; Ghousina, Ghousina; Atkiya, Naura; Selian, Rida Safuan; Hartati, Tengku; Septian, Ilham (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
This Community Partnership Empowerment Service activity aims to improve the competence of early childhood education (PAUD) teachers in developing eco-art-based thematic learning media through the utilization of used materials. The program was implemented in Aceh Besar Regency using a hands-on training and mentoring approach. The activity methods included partner needs analysis, providing conceptual materials, practicing diorama media creation, and evaluation through pre- and post-activity questionnaires, observations, and product assessments.  The results of the activity showed a significant and measurable improvement in teacher competence, as indicated by the increase in average scores from the moderate category (mean 2.5–2.9) to the good–very good category (mean 4.0–4.3). In addition, 88% of the diorama media produced were deemed suitable and effective for use in PAUD thematic learning, and 82% of teachers were able to independently develop eco-art–based learning media, while more than 80% of teachers expressed readiness and commitment to implement them sustainably in the classroom.  The impact of sustainability was also seen in the increased independence of teachers as developers of learning media based on local potential, thereby reducing dependence on manufactured media. This indicates that the program not only improved competencies but also strengthened sustainable teaching practices and teacher empowerment. Overall, this activity has an impact on improving the quality of PAUD thematic learning while strengthening the internalization of environmental awareness values from an early age through an eco-art-based teacher empowerment approach.